Análise participativa dos potenciais impactos socioambientais de parques eólicos marinhos (offshore) na pesca artesanal no estado do Ceará, Brasil - Xavier, Thomaz Willian de Figueiredo (2022)
Offshore wind farms (OWF) have already been established as an energy source in the world. In the Brazilian context, it is a potential sector for the generation of electricity. It is estimated that different socio-environmental impacts will arise involving coastal populations that make use of ocean and maritime resources around OWF projects. In this sense, different Brazilian institutions have already demonstrated the need to recognize the socio-environmental aspects related to the implementation of technology. Furthermore, in the selection of exclusion criteria for estimating the Brazilian offshore wind-energy potential, the lack of adequate data on fishing activity is verified. Thus, the objective of the research was to analyze the implementation of offshore wind farms on the coast of Ceará (Northeast Brazil), from political, social, and environmental understandings that involve this theme, considering possible impacts on adjacent coastal communities. Of an exploratory nature and based on a qualitative analysis of the data, it was articulated: the presentation of the expansion of offshore wind technology in the world, indicating the perspective of the development of the sector in the Brazilian context; the evaluation of the socio-environmental aspects of OWF projects located on the coast of Ceará; the implementation of a Participatory Socio-environmental Diagnosis (DSAP) through the use of SWOT – Strengths, Weaknesses, Opportunities and Threats – and social maps as an evaluative proposal; the appreciation of the potential socio-environmental impacts, considering the data obtained in the proposed DSAP and the consideration of concepts based on social justice to propose a discussion about the potential socio-environmental impacts. Data collection took place through nine participatory workshops carried out in four fishing colônias on the west coast of Ceará, where there are OWF projects. In all, there were 99 participants, all-male, aged between 22 and 55 years in August and September 2018 and January and March 2020. After collecting the information in the field, the data were scanned and validated with the community in March 2020 in new participatory workshops. Other qualitative methodologies were adopted in order to provide more robustness and validity to the data. In the elaboration of the SWOT matrices, 33 strengths, 28 weaknesses, 23 opportunities, and 21 threats were registered, related to the insertion of the OWFs studied. In the construction of the social maps, with a total of 3,805 km2 mapped, 42 distinct elements were registered, of which: 16 refer to the Fishing Activity; 16 correspond to the characteristics of the Territories and 10 are alluding to Existing or Potential Conflicts/Issues. Among the data acquired with the participation of fishermen, the following stand out: area with a cultural, symbolic, and economic interest in a planned location for the submarine cable; fishing spots and reports that fishing activity extends to the edge of the continental shelf; departure and return routes for artisanal vessels; reports of the presence of marine mammals and turtles; algae extraction sites by local residents and their potential for cultivation; among other features. The potential exclusion of an important fishing area due to the overlapping of the OWF became clear. It is possible to infer that, in the current form of planning of the evaluated OWFs, there may be more losses to fishermen than gains. However, the proposed DSAP allowed registering potential sectors for the construction of compensatory strategies. In this regard, it is important to emphasize the need for early consultation with fishermen and the potentially affected community. Finally, it is understood that the use of participatory methodologies, such as those evaluated here, can collaborate in the establishment of projects that are more aligned with the local socio-environmental reality. However, the guarantee that the use of such models will promote equitable and sustainable development, is up to the correct and fair absorption of the desires of fishermen and local residents.